Analisis Faktor Yang Mempengaruhi Kejadian Stunting Pada Balita Umur 24-59 Bulan Di Puskesmas Biak Muli Kabupaten Aceh Tenggara - Sebayang, Amenda; Hukamah, Siti (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
A multifactorial determinant analysis was conducted to identify contributions to the incidence of stunting-a condition of linear growth involution caused by chronic nutritional deficiencies and exposure to repeated infections-in children aged 24-59 months in the Biak Muli Health Center area, Southeast Aceh District, in 2023. This study adopted a cross-sectional survey design with a quantitative approach and descriptive-correlational design involving 85 mothers of toddlers as subjects. Data processing was conducted through univariate analysis, bivariate test using Chi-Square, and multivariate test with multiple logistic regression to identify significant determinants. Results showed that birth weight history (p=0.019; OR=4.051; CI 95%: 1.359-12.070), exclusive breastfeeding (p=0.009; OR=4.900; CI 95%: 1.571-15.285), parenting (p=0.012; OR=4.592; CI 95%: 1.475-14.298), and parental income level (p=0.024; OR=4.044; CI 95%: 1.303-12.557) were significantly correlated with stunting prevalence, while the variables of maternal knowledge (p=0.487), history of infection (p=0.101), and access to health services (p=0.095) did not show statistical significance. Family income was identified as the dominant predictor of stunting incidence in the child population in this region. Based on these findings, recommendations are directed at intensifying education to mothers of toddlers on comprehensive stunting prevention, including optimal nutrition interventions, environmental sanitation, and promotion of exclusive breastfeeding in the crucial period of early life, to reduce the risk of growth retardation in preschool.